Numerical comparison of methods for solving fractional differential-algebraic equations (FDAEs) - Ibis, Birol; Bayram, Mustafa (PERGAMON-ELSEVIER SCIENCE LTD, 2011)
In this paper, the variational iteration method (VIM) and the Adomian decomposition method (ADM) are implemented to give approximate solutions for fractional differential-algebraic equations (FDAEs). Both methods in applied mathematics can be used as alternative methods for obtaining analytic and approximate solutions for different types of fractional differential equations. This paper presents a numerical comparison between these two methods and the homotopy analysis method (HAM) for solving FDAEs. Numerical results reveal that the VIM and the ADM are quite accurate and applicable. Crown Copyright (C) 2011 Published by Elsevier Ltd. All rights reserved.
Keywords: Fractional differential-algebraic equations (FDAEs); Variational iteration method (VIM); Adomian decomposition method (ADM); Homotopy analysis method (HAM); ADOMIAN DECOMPOSITION METHOD; VARIATIONAL ITERATION METHOD; NONLINEAR OPERATORS; CONVERGENCE; DERIVATIVES; Mathematics